Earth, the sequel : the race to reinvent energy and stop global warming / Fred Krupp; Miriam Horn - Krupp, Fred
Krupp, longtime president of the Environmental Defense Fund, and Horn present a stirring and hopeful call to arms as they feature the bold innovators and investors who are reinventing energy and the ways we use it.